Do free healthcare policies play a role in expanding national health insurance enrollment among informal sector workers?: the case of the Afya Care pilot program in Kenya - Wamalwa, Phidelis; Strupat, Christoph; Yeboah, Edmund; Kuloba, MaryBennah; Mbuthia, Boniface; De Allegri, Manuela (BMC public health, 2025)
Several Sub-Saharan African countries have transitioned from fiscally unsustainable free healthcare policies to national health insurance schemes. These national schemes often expect informal sector workers to contribute directly to the scheme. Although enrollment in the national scheme is critical to achieving universal health coverage, informal sector workers’ inclusion remains challenging. In this paper, using the case of the Afya-Care free healthcare policy pilot in Kenya, we examine an issue that has thus far received limited attention in the literature: the extent to which earlier exposure to free healthcare policies shapes later informal sector workers’ decisions to enrol and contribute to a public health insurance scheme.